2007
DOI: 10.1007/s00113-007-1248-0
|View full text |Cite
|
Sign up to set email alerts
|

„Cutting out“ bei pertrochantären Frakturen – ein Problem der Osteoporose?

Abstract: In cases of bone density of >0.6 g/cm3 in the proximal femur (DEXA), the standard implants for the fixation of unstable trochanteric fractures could guarantee fixation without cutting out. The critical value of sufficient bone density in our few cases seems to be around 0.6 g/cm3 as measured by DEXA. Further investigation is needed to define the limits of bone mineral density for a successful osteosynthesis. An appropriate augmentation of the trabecular bone of the femoral head or a new design of the central l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 26 publications
1
48
1
12
Order By: Relevance
“…23,25 In our study there was no varus collapse accordance with the studies by Lee et al, Kim et al 25,26 Cement-augmented DHS have a different failure mode than screw cut-out in conventional DHS. Failures tended to be more related to delayed union, non-union and resultant side plate construct failure as concluded by Wu MH et al 27 In our study there were no cases of nonunion, the average time to union was 14.12 (12)(13)(14)(15)(16)(17) 28,29 They concluded no risk of thermal necrosis at the PMMA/bone interface or in the surrounding bone upto 6.0 cc PMMA. In a study by Lee et al using cement augmentation with DHS, with an average amount 13.7 ml of PMMA.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…23,25 In our study there was no varus collapse accordance with the studies by Lee et al, Kim et al 25,26 Cement-augmented DHS have a different failure mode than screw cut-out in conventional DHS. Failures tended to be more related to delayed union, non-union and resultant side plate construct failure as concluded by Wu MH et al 27 In our study there were no cases of nonunion, the average time to union was 14.12 (12)(13)(14)(15)(16)(17) 28,29 They concluded no risk of thermal necrosis at the PMMA/bone interface or in the surrounding bone upto 6.0 cc PMMA. In a study by Lee et al using cement augmentation with DHS, with an average amount 13.7 ml of PMMA.…”
Section: Discussionsupporting
confidence: 68%
“…12 In the past, various methods such as valgus osteotomy, valgus reduction with tension-band wiring, lateral wall reconstruction, and a variety of other techniques have been developed, in an attempt to reduce the rate of complications in the management of these fractures. [13][14][15][16] However, none of these have been able to completely address the problem of implant failure in osteoporotic patients, due to a superior screw cut out.…”
mentioning
confidence: 99%
“…After evaluating the relationship between osteoporosis and the incidence of dynamic hip screw, gamma nail, and PFN postoperative cutting, Bonnaire et al (2007) found that a bone mineral density of less than 0.6 g/cm 3 has a high fixation failure rate. Therefore, if the preoperative and postoperative procedures do not involve the systemic treatment of osteoporosis, postoperative functional exercise would not be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Fakat yaşlı hasta gurubunda instabil kırığa osteoporozun eşlik etmesi yüzünde rijid tesbit yön-temlerinin uygulama güçlükleri ve ameliyat sonrası implant sorunları ile karşılaşılabilmesi nedeni ile bu kırıkların tedavisinde hemiartroplastinin halen önemli bir yeri vardır. [4][5][6] Çalışmamızda, ileri yaş grubu intertrokanterik femur kırık-larının cerrahi tedavisinde proksimal femoral nail (PFN) ve hemiartroplasti uyguladığımız hastalarımızı ameliyat süresi ve kanama miktarı, erken ve geç dönem komplikasyonları, hastanede kalış süresi ve fonksiyonel sonuçları açısından değerlendirdik. Grup I' deki olgular kaynamama ve kötü kaynama, redüksi-yon kaybı-implant yetmezliği bakımından araştırıldı.…”
Section: Introductionunclassified